Influence of wear parameters on the tribological characteristics of jute/e-glass epoxy hybrid composites of different weave architecture. (2021) - Shenoy Heckadka, Srinivas; Nayak, Suhas Yeshwant; Samant, Rashmi; Malik, Abhinav; Aurichelle Magne Kam, Vanick
Abstract: In this study, sliding wear characteristics of the jute/E-glass reinforced epoxy based composites were investigated. Fiber mats with three weave patterns namely basket, plain and twill weave were considered. 10 layers of each weave pattern were used for composite fabrication using hand layup and compression moulding technique. Taguchi experimental design with L9 orthogonal array was considered. Three factors viz. normal load, sliding distance and sliding speed at three levels were analyzed for obtaining minimum specific wear rate. Normal load was the most significant factor influencing the response followed by sliding distance and sliding speed. ANOVA results supported the findings with p-values of less than 0.05 for the factors normal load and sliding distance while higher p-value for sliding speed. The percentage contribution of the factor normal load was in the range of 69% to 83%, followed by sliding distance (16% to 29%) and the least contribution was from the factor sliding speed in the range of 1 to 3% for different types of composites. Micrographs revealed different wear mechanisms like fiber pull-out, matrix cracking and furrows formation.